Ketogenic Diet in Refractory Focal Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The efficacy of the ketogenic diet in the treatment of intractable focal seizures was studied retrospectively in 34 patients (mean age, 7.5 yrs; range, 4 months to 29 yrs) and compared to 100 patients with generalized seizures at the Cleveland Clinic, OH.